THEORETICAL AND METHODOLOGICAL FOUNDATIONS OF TOURIST BUSINESS MANAGEMENT BASED ON PUBLIC-PRIVATE PARTNERSHIP (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article provides scientific opinions on the effective use of modern innovative means of public-private partnership mechanisms to increase the tourism potential of the country's regions, transform tourism into a strategic industry, increase tourism potential through the formation of a regional tourism cluster and improve the management of the tourism sector.